PARALLEL COMPUTING ON ANY DESKTOP. - Marowka, Ami (Communications of the ACM, 2007)
This article discusses the applications of parallel computing beyond the scientific and governmental research community. Developers using the OpenMP parallel programming model have created multithreaded applications in Beowulf clusters, a computer network technology harnessing hundreds of workstations banded together. Inexpensive and flexible in scale and administration, 72% of the top 500 supercomputers in 2006 were clusters. The author discusses how parallel computing differs from clusters and how it can now be adopted through the multicore processor for desktop computers and the OpenMP parallel programming model into Microsoft Visual C ++ 2005. A major technology shift is predicted.